My green alphabet book - Seth, Sreya (New Delhi The Energy and Resource Institute, 2013)
This title uses creativity and imagination to introduce the child to the alphabet through elements of the environment. Teacher's notes aid in inculcating concern for the environment, while easy-to-do 'green' activities make learning fun.
Keywords: Alphabet